1996
DOI: 10.1007/bf00179948
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical relationship between position of the sigmoid sinus and regional mastoid pneumatization

Abstract: In order to examine the relationship between the location of the sigmoid sinus (SS) and mastoid pneumatization, 25 adult temporal bones were dissected. Pneumatization was evaluated according to findings during dissections of three separate regions of the mastoid: i.e., the sinodural angle (SDA) area, inter-sinofacial area and mastoid apex. In addition, the SDA and distance between the SS and vertical portion of the facial nerve, were measured at the second genu (G) of the facial nerve, the junction (J) of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 7 publications
2
12
0
2
Order By: Relevance
“…This might be helpful, especially in revision cases of open cavity procedures [4]. This confirms Aslan et al's [12] findings, who determined this measurement to be 10.8 mm in formalin-preserved temporal bones. In the present study, the distance between the JB and mastoid segment of facial nerve was measured.…”
Section: Discussionsupporting
confidence: 81%
“…This might be helpful, especially in revision cases of open cavity procedures [4]. This confirms Aslan et al's [12] findings, who determined this measurement to be 10.8 mm in formalin-preserved temporal bones. In the present study, the distance between the JB and mastoid segment of facial nerve was measured.…”
Section: Discussionsupporting
confidence: 81%
“…Earlier reports (Shatz and Sade, 1990;Aslan et al, 1996;Ichijo et al, 1996;Sirikci et al, 2004) revealed that the h-ss distance was shorter in ears with poorly pneumatized mastoids. In this study, mastoid size was found to be significantly shorter in adults with COM than in adults with no evidence of otitis media (P < 0.000) (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 91%
“…When approaching the posterior cranial fossa and posterolateral cranial base, surface landmarks are used to locate the transverse-sigmoid sinus junction (Aslan et al, 1996;Ucerler and Govsa, 2006). The asterion is the mostly used landmark (Day and Manfred, 1998;Aysun et al, 2001).…”
Section: Discussionmentioning
confidence: 99%